A hagiopolite "proto-triodion" Quadragesima hymns in the new tropologion "Sin. Gr. ΝΕ ΜΓ 56+5" - Nikiforova, A. Ju. 1976-; Bauer, Samuel; Tucker, Gregory 19XX- (2024)
This article provides a first edition and English translation of the earliest known Greek Quadragesima collection, preserved in the 9th-century New Tropologion from St Catherine's Monastery on Sinai Gr. NE ΜΓ 56 and ΜΓ 5, and compares it to the previous stratum of hymns of the Old Iadgari, the Georgian Lectionary, contemporary Quadragesima collections in the 8th-9th c. St. Petersburg Rossijskaja Nacional’naja biblioteka [RNB] Gr. 87, and the posterior collections, Constantinopolitan Triodia RNB Gr. 712, Sinai Gr. 734-735, and Vat. Gr. 771, speculating about the development of the structures, hymn types, and interpretations of this hymnographical book of the Byzantine rite.
Ohne Seitenzählung nach Seite 142: 5 farbige Illustrationen